2008
DOI: 10.1117/12.789372
|View full text |Cite
|
Sign up to set email alerts
|

A theory for image persistence in HgCdTe photodiodes

Abstract: Image persistence, an elevated dark current caused by prior illumination, has been a chronic problem in near infrared focal plane arrays. It has the potential to interfere with astronomical surveys requiring precision photometry, astrometry and/or shape measurement. We posit a mechanism whereby charge is captured by traps exposed to carriers as the depletion width shrinks when photo-generated charge accumulates on the electrically isolated photodiode. After the depletion width is reestablished by resetting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 2 publications
0
39
0
Order By: Relevance
“…These studies aimed to describe the effects of charge trapping on the data by fitting empirical functions to the observed trends, an approach that only works imperfectly and only applicable within sets of self-similar observations. The model we introduce here invokes the same physically-motivated conceptual picture as previous studies(e.g., Smith et al 2008a); however, our approach differs from the past qualitative and quantitative models in two important aspects: First, our model assumes that charge trapping occurs immediately after the photons are absorbed and not later, i.e., charge trapping occurs only when the detector is illuminated. This difference results in a different behavior of the detector, which we demonstrate is more consistent with the existing observations than the predictions of the traditional model that assumes continuing trapping even in the non-illuminated state of the detector.…”
Section: Physical Backgroundmentioning
confidence: 93%
See 4 more Smart Citations
“…These studies aimed to describe the effects of charge trapping on the data by fitting empirical functions to the observed trends, an approach that only works imperfectly and only applicable within sets of self-similar observations. The model we introduce here invokes the same physically-motivated conceptual picture as previous studies(e.g., Smith et al 2008a); however, our approach differs from the past qualitative and quantitative models in two important aspects: First, our model assumes that charge trapping occurs immediately after the photons are absorbed and not later, i.e., charge trapping occurs only when the detector is illuminated. This difference results in a different behavior of the detector, which we demonstrate is more consistent with the existing observations than the predictions of the traditional model that assumes continuing trapping even in the non-illuminated state of the detector.…”
Section: Physical Backgroundmentioning
confidence: 93%
“…The width of the undepleted regions (see Figure 1 of Smith et al 2008a) increases with fluence level, which potentially enlarges the number of available traps. Indeed, Long et al (2012Long et al ( , 2015a showed that the persistence of the WFC3 IR detector surged when fluence reached near saturation, which could suggest significant trap density increase at saturation.…”
Section: The Relationship Between the Number Of Traps And Fluence Levelsmentioning
confidence: 99%
See 3 more Smart Citations